Role of Circulating Tumor DNA in Gastrointestinal Cancers: Update From Abstracts and Sessions at ASCO 2018 - Shahjehan, Faisal; Kamatham, Saivaishnavi; Kasi, Pashtoon Murtaza (Frontiers in Oncology, 2019)
Background: The hallmark of circulating tumor DNA (ctDNA) is its rapid turnaround and non-invasive nature. According to American Society of Clinical Oncology (ASCO) and College of American Pathologists joint ctDNA review published in March 2018, there is not sufficient evidence to support the use of ctDNA in practice for GI cancers. However, there were numerous studies presented at ASCO Annual Meeting supporting its value. We aimed to summarize on its role in the management of gastrointestinal cancers based on the studies presented recently. We limited our search to keywords ‘ctDNA’, ‘circulating tumor DNA’, ‘cell-free DNA (cfDNA)’ and/or ‘liquid biopsy’, at the 2018 ASCO Annual Meeting library abstracts and presentations. There were 35 studies that revolved around ctDNA as a diagnostic tool, prognostic marker and/or a measure of tumor heterogeneity in gastrointestinal cancers. Depending on the assay used, the results of several studies showed that ctDNA was able to identify relevant mutations or fusions including RAS, HER2/Neu, BRAF, MET, BRCA2, APC, TP53, ALK, ROS1, PTEN and NF1. The prognosis in terms of tumor mutation burden, objective response rate, metastasis and survival were also estimated by various studies based on ctDNA. The findings showed that higher baseline ctDNA levels and/or increased number of mutations detected in ctDNA were associated with poor survival and multi-site metastasis. Right-sided colon cancer was associated with higher number of mutations in ctDNA than left-sided colon and rectal cancers. Similarly, tubular adenocarcinoma subtype of gastric cancer was more likely to have higher ctDNA levels than signet-ring cell subtype